Praktik Pinjaman dalam Hukum Perniagaan Islam: Analisis Kualitatif Kepatuhan Syariah di Sektor Bisnis Modern: Praktik Peminjaman dalam Hukum Komersial Islam: Analisis Kualitatif terhadap Kepatuhan Syariah dalam Sektor Bisnis Modern - Rangkuti, Mhd. Royhan; Saputra, Ramadi; Hasibuan, Abdul Nasser (Universitas Sumatera Barat, 2025)
This study aims to explore lending and debt practices in Islamic commercial law within Indonesia’s modern business sector, focusing on Micro, Small, and Medium Enterprises (MSMEs) and Islamic financial institutions. The research addresses the ongoing tension between the idealism of Sharia principles emphasizing fairness, transparency, and the prohibition of riba and the pragmatic realities of business financing. A descriptive qualitative approach with a case study design was applied. Data were collected through semi-structured interviews with MSME entrepreneurs and Islamic finance practitioners, supported by limited field observations due to incomplete access to some respondents. The findings reveal that the understanding of Sharia principles among MSME actors remains partial, often limited to the prohibition of interest, while practical lending is still dominated by conventional banks. Although several Islamic financing contracts, such as murabahah and qardul hasan, are applied, administrative fees and procedural complexity remain barriers to full Sharia adoption. Low Islamic financial literacy and limited product innovation also hinder broader engagement with Islamic financing. Nevertheless, participants noted that Sharia-based loans provide spiritual comfort and ethical reassurance compared to interest-bearing credit systems.